Training and evaluation of robot-based psychological intervention program for preventing child sexual abuse - Mohammad Tahan; Gholamali Afrooz; Jafar Bolhari (Child Protection and Practice)
Background and purpose: Preventing child sexual abuse is a health and medical priority in many countries. The risk of sexual abuse can be markedly reduced through education, awareness, and skill-building for children. The purpose of this study was to train and evaluate a robot-based psychological intervention program for preventing child sexual abuse. Methods: This study had a semiexperimental design that included pre- and posttests as well as a control group. A stratified random sample of 80 individuals was drawn from the population of eight-to ten-year-old children in Ghaen, Iran, in 2018. Subsequently, the sample was randomly divided into two experimental groups and two control groups. The experimental group participated in a robot-based psychological intervention program, for a total of 10 sessions. The control group received no intervention. The tool used to measure children's knowledge and awareness of sexual abuse was a custom-designed questionnaire developed by Tahan (Tahan, 2023). Participants completed the questionnaire in the pretest, posttest, and follow-up stages. The collected data were analyzed using repeated measures ANCOVA in SPSS (v.25). Results: The findings demonstrated that educating children about sexual abuse was effective in enhancing their knowledge of appropriate and inappropriate touching (p < 0.01). Furthermore, the robot-based cognitive-behavioral intervention program for the prevention of child sexual abuse was effective (p < 0.01). Conclusion: The psychological intervention program increased children's knowledge and awareness concerning the prevention of sexual abuse and associated coping skills. Furthermore, psychological intervention programs were effective in preventing child sexual abuse.